The teaching of French through storytelling: Acquisition strategies within the Algerian school - Gaoudi, Fella (El Omda in Linguistics and Discourse Analysis, 2025)
The teaching of storytelling within the Algerian school starts from the first cycle, hence the importance attributed to this type of text in the training of our learners and especially in the teaching/ learning of FLE in Algeria. This type of text admits a stereotype in its structure, which will itself participate in facilitating and anchoring the form of the textual typology of the tale through all the pedagogical activities made in class and from which this little learner begins to memorize the scheme and structure of the tale by, first his first contact with the tale that will be during the oral comprehension session where he will listen to a story through the tale (a listening session), then in a reading session where, we try to get the learner involved and this is what we will explain throughout our communication